Factors Contributing to the Entrepreneurial Development in Bangladesh: A Study on Rajshahi City - Kabir, A.N.M. Jahangir (Asian Business Review, 2018)
This paper attempts to examine the impact of pull and push factors on the entrepreneurial development process. The pull factor “earning extra money for family” has appeared as the most important motivating factor for undertaking an entrepreneurial activity. Both the factors such as “self-employment with economic freedom” and “Less complex and more profitable” have emerged as the second most important factors contributing to an entrepreneurial phenomenon, followed by the factor “Use of personal knowledge and experience” being the third most important factor. The support from the government and the financial support from the bank have been found to be little to do with the respondents’ undertaking the entrepreneurial activity. The respondents with experience of ‘10 years and above’ have ranked the factors ‘Less complex and more profitable’ and ‘Earning extra money for family’ as the most important and second most important motivating factors respectively. Whereas the respondents without any experience and with experience below ten years have ranked the factors ‘Earning extra money for family’ and ‘Self-employment with economic freedom’ in the first or second place contrariwise. Irrespective of the nature of businesses they are engaged in, all the respondents have viewed the factor ‘Curse of unemployment’ as the most important factor that compelled them to undertake the entrepreneurial activity.